CADRE TRAINING TO IMPROVE KNOWLEDGE AND SKILLS IN POST-STROKE PATIENT CARE - Luluk Widarti; Suprianto Suprianto; Ani Intiyati; Ferry Kriswandana; Dony Sulystiono; Muhammad Afif Hilmi Masyafahani (Universitas Airlangga, 2026)
Introduction: Noncommunicable diseases, particularly stroke, have become a public health issue due to the increasing number of post-stroke patients requiring long-term care. However, the ability of Posbindu PTM cadre to care for patients remains limited due to a lack of knowledge and skills. Therefore, this community service initiative aims to enhance the knowledge and skills of Posbindu PTM cadre in caring for post-stroke patients. Methods: This community service program was carried out in Tanggul Village in collaboration with Posbindu PTM cadres, involving a total of 30 participants. Communication, Information, and Education (CIE) activities related to holistic post-stroke patient care were conducted. The variables measured were the cadre’ knowledge and skills in caring for post-stroke patients. Measurements were taken using questionnaires and observation sheets through a pretest and posttest design. Data were analyzed using the Wilcoxon test to determine differences before and after the intervention. Results: The results of the intervention showed a significant improvement in the knowledge and skills of Posbindu PTM cadres regarding the care of post-stroke patients. The results showed a p-value < 0.05 for all variables, indicating a significant difference between pre- and post-intervention. Conclusion: The CIE-based intervention, combined with physical rehabilitation training and nutritional coaching, effectively improved the knowledge and skills of Posbindu PTM cadres in post-stroke patient care, indicating enhanced readiness of cadres to provide holistic, community-based care for post-stroke patients. KEYWORDS balanced nutrition; healthy home; health cadres; rehabilitation; stroke